Social Capital and Location as Determinants in Improving MSME Performance - Khusaini, Khusaini; Lestari, Lina Widya; Widiarti, Aniek; Suherman, Agus (Faculty of Economics, Universitas Negeri Indonesia,Indonesia, 2022)
Improving MSME (Micro, Small, and Medium Enterprises) performance is essential for business owners to increase their income and welfare. However, recently, the company’s performance tend to decrease, particularly among MSMEs’ businesses, resulting in a significant reduction in the country or region’s the economy and household income. Based on that reason, this research was conducted to examine the impact of social capital, location, and control variables on the MSMEs performance. Using the incidental sampling technique, the authors collected data from as many as 131 samples located and opened a business in North Tangerang. The distributed instrument has been initially checked for its validity and reliability. Multiple regression was employed to analyze the data. The finding showed that social capital and location significantly determined the improvement of MSME performance. The greater the accumulation of social capital and precision of business location, the greater the company’s performance. These findings contribute to providing important information considering social capital and location as determinant factors for future policies and business plans.